HUBUNGAN KEBIASAAN MEROKOK TERHADAP VOLUME OKSIGEN MAKSIMAL (VO2MAX) PADA MAHASISWA JURUSAN PENKESREK UNESA ANGKATAN 2015 - JAKFAR ZUHDI, ALEX (Jurnal Kesehatan Olahraga, 2016)
The total number of smokers has been increasing, teenagers nowadays especially. The increasing total numbers of smokers is caused by teenagers’ mindset that smoking is a part of social life and life style, meanwhile there are varied effects caused by smoking habit for example lung cancer, chronic bronchitis, asthma, and many more. Once our lung is attacked by disease, our lung cannot work well anymore, the VO2 max will be decreasing either. The aim of this research is that to identify whether there is any correlation between smoking habit and VO2 max. In this research, correlative approach and quantitative descriptive reasearch would be applied. There are 160 State University of Surabaya students of Health Education and Recreation Department generation 2015 would be the population of this research. The 30 samples would be gained by using Purposive Sampling Technique. Questionnaire method would also be apllied in this research to know the degree of the active smokers and MFT test to know the degree of VO2 max. The result of this research shows that the average of smoking habit degree of the active smokers is around 41,27 and the degree of VO2 maxis 36,88. Based on the correlation test, it is known that the coefficient of correlation itselft is -0,45, so we can claim that it they have medium correlation. While, the minuteness sign on the coefficient degree shows that there is a contrary correlation between active smoking habit and VO2 max degree. In order to examine the coefficient of correlation, T-Test pattern with significance level would be applied. Based on the counted result, it is known that value of t-count = 2,667 and we gain 1,701 from t-table with df =28. Due to the value of t-count > t-table (2,667 > 1,701), it is a kind of significant correlation coefficient. Based on the calculation of coefficient determination, actively smoking gives such a contribution towards VO2 max in the amount of 20,25%. Therefore, the researcher conclude that smoking habit of the State University of Surabaya students of Health Education and Recreation Department generation 2015 as the population in this research bring some effects towards VO2 max. From the two variables of this research, we can know that there is a significant correlation between that two variables which is significantly contrast, so it is suggested for everyone to stop smoking.